SPECIFIC CHARACTERISTICS OF THE DEVELOPMENT OF CHILDREN WITH HEARING IMPAIRMENT (Academia Science Repository, 2023)
The article describes the specific characteristics of children with hearing impairment, ways and methods of early development. It is given the importance of early education, as well as information about the basic rules that parents should know about the preschool education of children with hearing impairment.